How Tight Are the Ties that Bind Stakeholder Groups? - Wolfe, Richard A.; Putler, Daniel S. (Organization Science, 2002)
The purpose of stakeholder management is to facilitate our understanding of increasingly unpredictable external environments, thereby facilitating our ability to manage within these environments. We argue that a powerful implicit assumption within the stakeholder literature—that priorities within role-based stakeholder groups are relatively homogeneous—blurs our understanding of organization-stakeholder relationships. Two important and related areas of concern are presented. The first involves the primacy of role in stakeholder definition. This role primacy approach to stakeholder definition is appropriate if, for a particular issue, role-based stakeholder group members have similar priorities. Individual and collective self-interest provides a rationale for this assumption. However, an important problem with this approach arises in situations in which self-interest is not the primary motivator of individuals' priorities. In these instances, subgroups within different role-based stakeholder groups might have more similar priorities than either subgroup has with others within their role-based stakeholder group. In these situations the role primacy approach impedes, rather than facilitates, an understanding of our environment. Our second concern is related to insufficient rigor in the application of stakeholder analysis. Most stakeholder studies, both theoretical and empirical, fall short in the determination of relevant interests and the subsequent subdivision of role-based stakeholder groups into rigorously defined specific stakeholder groups. Having suggested that the role primacy approach to stakeholder definition is less than ideal, we examine the extent to which, and the conditions under which, roles are likely to determine priorities, and thus, the likelihood of relatively homogeneous priorities within role-based stakeholder groups. In addition, we present an illustrative empirical analysis of stakeholder group priorities. The illustrative study is conducted within the context of intercollegiate athletics. Related literature and our empirical results indicate that role-based self-interest frequently is not a sufficient "binding tie" of stakeholder groups. Given this background, we present an alternative approach to stakeholder analysis that borrows heavily from the customer segmentation literature of marketing. Our alternative approach can accommodate heterogeneous priorities within role-based stakeholder groups.